Autism is not associated with poor or enhanced performance on the Iowa Gambling Task: A Meta-Analysis. (June 2020) - Zeif, Dana; Yechiam, Eldad
Highlights: Fourteen independent studies administered the IGT to ASD and control groups. Individuals with ASD and controls did not differ in decision performance on the IGT. Individuals with ASD only showed a slight performance drop in the first block. Differences between studies were not moderated by IQ, age, gender, or study quality. Abstract: Individuals with Autism Spectrum Disorder (ASD) report difficulties in making routine decisions. Yet there is a controversy about whether their decision performance is impaired or enhanced compared to typically developing individuals. We focused on studies of the Iowa Gambling Task (IGT) where contrary arguments have been made in this regard. In a meta-analysis, we examined differences between high functioning individuals with ASD and controls in decision performance (choice of long-term advantageous options) and choice switching on the IGT. The analysis encompassed 14 studies involving 433 participants with ASD and 500 controls. The results showed virtually no difference in IGT performance between groups ( d = 0.04), except for a slight disadvantage in the first block of trials for the ASD group ( d = -0.16). We also found a non-significant trend towards increased choice switching in the ASD group ( d = -0.37) that may be examined in future research. In sum, decision performance on the IGT is similar in individuals with ASD and controls, though their strategy may differ.